Private investments in South Africa - An empirical analysis of investment behaviour - Innocent Sitima,; Ronney Ncwadi, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
This study examines the determinants of private investments in South Africa in an attempt to understand if the possibility of the Tobin Q can be used to interpret the patterns and trends in the South African business and residential subsections of investments. Using the South African annual time series data from 1960- 2010, the dynamic investment equation is estimated using general- to- specific ARDL approach to magnify the connection and trends. The study established that combined asset prices and the levels of business investment affect the long run investment performance rather than the Tobin Q. In the short run the lagged values of the Q, business investment and residential investments seemed to be the influential driving forces of private investment in South Africa. Even if the capital reserves in South Africa seem to be healthy, there is always a dire call for policy to be geared in the direction of credit accessibility to guarantee a supplementary conducive investment climate.